Effect of a nursing intervention based on nutritional support on biochemical parameters and quality of life in patients with hyperthyroidism combined with diabetes mellitus - Yang, Huanjing; Feng, Jiajia (Frontiers in Endocrinology, 2025)
This study was conducted to study the effect and of nursing intervention on biochemical parameters, complications and quality of life in patients with hyperthyroidism combined with diabetes mellitus. This study included 112 patients who were treated for diabetic hyperthyroidism from April 2022 to April 2024 in our hospital. The control group was given routine care, and the nursing group was given nutritional, psychological and exercise nursing interventions on the basis of the control group. The blood glucose, thyroid function, nutritional status, complications, nursing satisfaction and quality of life of patients in different groups were compared. The analysis show that nursing intervention can effectively improve the patients’ blood glucose level, thyroid function and nutritional status, and reduce the incidence of complications so as to improve the patients’ quality of life. In conclusion, nursing intervention based on nutritional support can successfully upgrade the condition and prognosis of patients with hyperthyroidism combined with diabetes mellitus and improve nutritional status and quality of life.